Reimbursed Medication Adherence Enhancing Interventions in European Countries: Results of the EUREcA Study - Ágh, Tamás; Hadžiabdić, Maja Ortner; Garuoliene, Kristina; Granas, Anne Gerd; Aarnio, Emma; Menditto, Enrica; Gregório, João; Barnestein-Fonseca, Pilar; Mevsim, Vildan; Kardas, Przemysław; , European Network to Advance Best Practices and Technology on Medication Adherence (ENABLE) (Frontiers in Pharmacology, 2022)
Introduction: Current literature lacks detailed understanding of the reimbursement framework of medication adherence enhancing interventions (MAEIs). As part of the ENABLE COST Action, the EUREcA (“EUropen REimbursement strategies for interventions targeting medication Adherence”) study aimed to provide an in-depth overview of reimbursed MAEIs currently available in European countries at national and regional levels and to pave the way for further MAEIs to be implemented in the future. Methods: A web-based, cross-sectional survey was performed across 38 European countries and Israel. The survey questionnaire was developed as a result of an iterative process of discussion informed by a desk review. The survey was performed among invited ENABLE collaborators from June to July, 2021. Besides descriptive analysis, association between country income and health care expenditure, and the availability of reimbursed MAEIs were also assessed. Results: The survey identified 13 reimbursed MAEIs in 9 countries: multi-dose drug dispensing (n=5), medication review (n=4), smart device (n=2), mobile application (n=1), and patient education (n=1). The median GDP per capita of countries having ≥1 reimbursed MAEI was significantly higher compared to countries having no reimbursed adherence intervention (33,888 EUR vs. 16,620 EUR, respectively; P=0.05). Conclusions: Our findings highlight that to date only a small number of MAEIs have been reimbursed in European countries. Comprehensive health technology assessment recommendations and multi-stakeholder collaboration could help removing barriers related to the implementation and reimbursement of MAEIs.